Depth-Dependent Diversity Patterns of Rocky Subtidal Macrobenthic Communities Along a Temperate Fjord in Northern Chilean Patagonia - Villalobos, Vicente I.; Valdivia, Nelson; Försterra, Günter; Ballyram, Stacy; Espinoza, Juan Pablo; Wadham, Jemma L.; Burgos-Andrade, Katherine; Häussermann, Vreni (Frontiers in Marine Science, 2021)
Understanding the distribution of biodiversity along environmental gradients allows us to predict how communities respond to natural and anthropogenic impacts. In fjord ecosystems, the overlap of strong salinity and temperature gradients provides us with the opportunity to assess the spatial variation of biodiversity along abiotic environmental gradients. However, in Northern Chilean Patagonia (NCP), a unique and at the same time threatened fjord system, the variation of macrobenthic communities along abiotic environmental gradients is still poorly known. Here, we tested whether macrobenthic species diversity and community structure followed systematic patterns of variation according to the spatial variation in salinity and temperature in Comau Fjord, NCP. A spatially extensive nested sampling design was used to quantify the abundance of subtidal macrobenthic species along the fjord axis (fjord sections: head, middle, and mouth) and a depth gradient (0–21 m). The vertical structure of the water column was strongly stratified at the head of the fjord, characterized by a superficial (depth to ca. 5 m) low-salinity and relatively colder layer that shallowed and decayed toward the mouth of the fjord. The biotic variation followed, in part, this abiotic spatial pattern. Species richness peaked at high salinities (>27 psu) between 5 and 10 m in the head section and between 15 and 21 m in the middle and mouth sections. Diversity and evenness were also highest at these salinities and depth ranges in the head and middle sections, but at shallower depth ranges in the mouth. Information theory-based model selection provided a strong empirical support to the depth- and section-dependent salinity, but not temperature, effects on the three biodiversity metrics. Erect algae and the edible mussel Aulacomya atra numerically dominated in shallow water (0–3 m) at the head and the middle of the fjord, coinciding with the horizontal extension of the low-density water layer—these taxa were further replaced by the crustose algae Lithothamnion sp. and deep-dwelling suspension filters (e.g., corals, polychaetes, and sponges) along depth gradient. Macrobenthic biodiversity correlated, therefore, with the influence of freshwater inputs and the density-driven stratification of the water column in this ecosystem. The spatially variable (across both, horizontal and vertical fjord axes) thresholds observed in our study question the widely accepted pattern of increasing biodiversity with increasing distance from the head of estuarine ecosystems. Finally, non-linear environmental stress models provide us a strong predictive power to understand the responses of these unique ecosystems to natural and anthropogenic environmental changes.